Mediation of Company Size in the Influence of Profitability and Leverage on Company Value (Empirical Study on Manufacturing Companies in the Basic Industrial and Chemical Sectors, 2020-2022) - Fauziah, Nadia; Azhar, Meilisa Mulyawati; Maiyaliza, Maiyaliza (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to understand whether company size mediates the effect of profitability and leverage on company value in manufacturing companies in the basic industrial and chemical sectors during the 2020-2022 period. This type of research uses quantitative research using secondary data recorded systematically in the form of a time series, namely from 2020-2022 obtained from the official IDX website (www.idx.co.id) with associative cause and effect as a form of research. Based on the test results using the T Test, it was found that Return on Equity (ROE), Debt to Equity Ratio (DER), and Company Size had a significant effect on company value with significance values ​​of 0.0043, 0.0000 respectively, and 0.00005. This shows that Hypotheses 1, 2, and 3 can be accepted. However, the influence of ROE and DER on company size does not have a significant effect on company value with significance values ​​of 0.4481 and 0.8949 respectively, so Hypotheses 4 and 5 are rejected. Based on the test results using the Sobel Test, it was found that company size was unable to mediate the influence of ROE and DER on company value with p-values ​​of 0.64 and 0.45 respectively, indicating that Hypotheses 6 and 7 were rejected.